Potential of Health Resort Treatment of Cardiovascular Diseases - DAMADAEVA, Angela Sergeevna; MAGOMEDOVA, Saida Alirzaena; MOLLAEVA, Naida Radjabovna (Journal of Environmental Management and Tourism; Vol 8 No 4 (2017): JEMT Volume VIII Issue 4(20) Summer 2017DO - 10.14505//jemt.v8.4(20).05, 2017)
The current study is devoted to the problems of using the health resort potential of the Republic of Dagestan for the implementation of cardiovascular rehabilitation programs. The main objective of this study is to develop measures that improve accessibility of cardiac rehabilitation for population and increase the efficiency of using the health resort facilities of the region. Methods of statistical data analysis, retrospective and comparative analysis of indicators are used in the study. Using these methods, the results on the incidence of cardiovascular diseases (CVDs) and the development of the health resort facilities of the Republic of Dagestan are obtained. Results of the study of the incidence of CVDs in the Republic of Dagestan allow to make a conclusion that CVDs are the leading cause of mortality and disability in the Republic of Dagestan. Dagestan is a relatively prosperous region of Russia in terms of prevalence of CVDs, disability and mortality of the population from CVDs. Nevertheless, the death rate from CVDs remains quite high. Results of the analysis of health resort facilities show that the existing recreational potential for implementing cardiac rehabilitation programs in the region is not being used efficiently enough. The following is proposed as the main areas of development of the cardiac health resort infrastructure: to develop a cardio health resort of the regional level that implements specialized rehabilitation programs; to comprehensively modernize the health resort facilities that implement rehabilitation programs for patients with CVDs; to develop measures to encourage the use of undeveloped land plots and unfinished construction sites located in the resort areas of the Republic of Dagestan. Regional authorities need to take measures to create favorable conditions for the industry infrastructure.